Green Accounting, GCG, and Firm Performance: Capital Structure Mediation and Firm Size Moderation - Raditya Dheva Eka Setya Nugraha; Zulfikar; Triyono (Universitas Muhammadiyah Malang, 2026)
Purpose: This study aims to empirically measure the influence of green accounting and GCG on performance, with capital structure as a mediating variable and size as a moderating variable, across cyclical and non-cyclical sectors of companies listed on the IDX for the 2019-2023 period. Methodology/approach: This study uses a quantitative approach with partial least squares-structural equation modeling (PLS-SEM). Using purposive sampling to collect data observations of 41 companies in 5 years, with a total of 205 observations. Findings: green accounting does not directly affect performance, while GCG has a significant effect on performance and capital structure. Capital structure mediates the relationship between green accounting and GCG to performance. The size of the company does not moderate. Practical implications: Companies must optimize their capital structures and strengthen GCG to support sustainable investment; Green Accounting needs to be integrated into financial planning to improve the quality of sustainability reporting. Regulators and financial institutions are expected to incentivize and strengthen policies on capital structure that are relevant for companies. Originality/value: This study structurally examines green accounting and GCG on performance, with capital structure as a mediating variable and size as a moderating variable, a combination that has not been explored in prior studies.